QUATERNARY PREVENTION IN PRIMARY HEALTH CARE - Kelly Duarte Lopes Pires, Greicy; Leonardo de Oliveira Dias, Cristiano; Sousa Pinheiro, Jeferson; Alves Barbosa Teles, Mariza; Jardim Neiva, Ricardo; Cardoso dos Santos, Rafael; Vieira de Oliveira, Valdira; Dayane Guimarães Fonseca, Adelia; Gabriel Santos Silva, Diogo; Dias Gomes, Gabriella; Palmeira Eleutério, Cynthia; Gonçalves Ferreira, Aline; et al. (Health and Society, 2026)
The present study aimed to analyze the impact of incorporating the principles of quaternary prevention into primary health care. An integrative literature review was conducted, analyzing articles retrieved from the secondary databases Virtual Health Library, Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online, and Online System for Search and Analysis of Medical Literature using the descriptors quaternary prevention; primary health care; and basic care. In summary, P4 in primary health care has a profound and transformative impact, mainly by: reducing iatrogenesis – by encouraging the practice of non-intervention in cases of diagnostic uncertainty or marginal clinical benefit, P4 protects the patient from excessive tests, overdiagnosis, and polypharmacy, reducing the risk of adverse effects and the burden of unnecessary treatments; improving screening – P4 promotes individualized and critical screening, prompting primary care professionals to question the blind application of universal protocols and to consider life expectancy, context, and patient values before initiating or continuing a preventive intervention; and strengthening the professional-patient relationship – the emphasis on shared decision-making and transparency about risks and diagnostic uncertainties empowers the patient and reinforces trust in the healthcare team. The analysis of the impact of incorporating the principles of quaternary prevention into primary healthcare shows that this concept goes beyond a mere ethical approach, establishing itself as an essential pillar for quality, safety, and sustainability